Peace be still : how James Cleveland and the Angelic Choir created a gospel classic - Marovich, Robert M. (Music in American life, 2021)
In September of 1963, Reverend Lawrence Roberts and the Angelic Choir of the First Baptist Church of Nutley, New Jersey, teamed with rising gospel star James Cleveland to record Peace Be Still. The LP and its haunting title track became a phenomenon. Robert M. Marovich draws on extensive oral interviews and archival research to chart the history of Peace Be Still and the people who created it. Emerging from an established gospel music milieu, 'Peace Be Still' spent several years as the bestselling gospel album of all time. As such, it forged a template for live recordings of services that transformed the gospel music business and Black worship. Marovich also delves into the music's connection to fans and churchgoers, its enormous popularity then and now, and the influence of the Civil Rights Movement on the music's message and reception.
Keywords: Cleveland, James : Peace be still; First Baptist Church (Nutley, N.J.) : Angelic Choir; Gospel music : History and criticism; Gospel music : New Jersey : History and criticism